2008
DOI: 10.1530/eje-08-0072
|View full text |Cite
|
Sign up to set email alerts
|

Relation of 25-hydroxyvitamin D and parathyroid hormone levels with metabolic syndrome among US adults.

Abstract: This relation was unchanged after additional adjustment for PTH level (OR, 0.26; 0.15, 0.44; P trend !0.001) and did not differ by sex (P interaction 0.6) or age (! or R50 years; P interaction 0.2). In contrast, the multivariable-adjusted odds for MetSyn increased with increasing PTH among older men (P trend 0.004), but not younger men (P trend 0.4) or women regardless of age (P trend 0.4 in younger and older women). Conclusions: These data suggest an inverse association of 25(OH)D with MetSyn, independent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
166
11
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(198 citation statements)
references
References 46 publications
17
166
11
4
Order By: Relevance
“…Many studies showed that in patients with metabolic syndrome, vitamin D level is lower, while some other studies rejected this hypothesis. In a study on 1654 Americans, [24][25][26] the lower levels of vitamin D was observed in patients with metabolic syndrome; the result was in agreement with those of some other studies. In a study by Moy on 380 individuals, subjects with vitamin D deficiency were at higher risk for the development of metabolic syndrome (OP = 1.73); in addition, BMI, waist circumference, and TG level were significantly different among the ones with normal and vitamin D deficiency [27].…”
Section: Discussionsupporting
confidence: 90%
“…Many studies showed that in patients with metabolic syndrome, vitamin D level is lower, while some other studies rejected this hypothesis. In a study on 1654 Americans, [24][25][26] the lower levels of vitamin D was observed in patients with metabolic syndrome; the result was in agreement with those of some other studies. In a study by Moy on 380 individuals, subjects with vitamin D deficiency were at higher risk for the development of metabolic syndrome (OP = 1.73); in addition, BMI, waist circumference, and TG level were significantly different among the ones with normal and vitamin D deficiency [27].…”
Section: Discussionsupporting
confidence: 90%
“…Several studies reported that 25(OH)D 3 was inversely related to percentage body fat (37,38), elevated BP (39-41), elevated glucose or IR (11,(42)(43)(44), and triglycerides (45) and positively associated with HDL-cholesterol (42). In particular, using data from the Third National Health Examination and Nutrition Survey (NHANES) (46). However, the explanation of the inverse associations of metabolic derangements with deficiency of vitamin D is very complex.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of the mechanisms by which 25(OH)D and the IGF-1 and IGF binding proteins interact is warranted to discover their influence on insulin and glucose secretion and/or sensitivity. Another recent cross-sectional analysis of 1654 men and women reported a substantially lower OR for the MetS in the highest quintile of s25(OH)D (median 88·0 nmol/l; OR 0·15) compared with the lowest quintile (median 26·8 nmol/l; OR 0·46) (39) (40 -42) . McGill et al (41) showed in 243 obese adults, 80 % of whom were women (age 47·6 (SD 12) years), that while s25(OH)D concentration was inversely associated with waist circumference, BMI and HbA 1c , there was no association with the MetS.…”
Section: Cardiometabolic Syndromementioning
confidence: 97%
“…Low vitamin D status has been associated with an increased risk of the MetS (Ford et al (11) ; Forouhi et al (37) ; Hypponen et al (38) ; Reis et al (39) ; S Muldowney, A Lucey, G Paschos, et al, unpublished results; M Kiely, S Muldowney, TR Hill, et al, unpublished results). Using data from National Health and Nutrition Examination Survey (NHANES) III in almost 8500 adults (aged $ 20 years), Ford et al (11) observed subjects in the lowest quintile of s25(OH)D (# 48·4 nmol/l) were twice as likely to have the MetS compared with those in the highest quintile ($ 96·4 nmol/l).…”
Section: Cardiometabolic Syndromementioning
confidence: 99%